The Relationship Between Market Orientation, Learning Orientation and Business Model Innovation: A Case Study Of Restaurants - Hotels in Ho Chi Minh City - Quang Huan, Ngo; Tan Phong, Vo; Luu Hoang Giang, and (British Journal of Marketing Studies, 2020)
Currently, people’s lives greatly improved, which has led to a fast-growing tourism demand, which requires the tourism industry to grow faster than the GDP growth rate, in which the hotel business system holds a prominent position. Therefore, the objective of this study is to explore the relationship between market orientation, learning Orientation to business model innovation of restaurants and hotels in Ho Chi Minh City (HCMC). The researchers surveyed 600 managers related to restaurants and hotels in HCMC. They answered 12 questions, and 545 samples processed. The data got from November 2019 to January 2020 in HCMC. Simple random sampling technique. The data analyzed Cronbach’s Alpha and the exploratory factor analysis (EFA), and multiple regression analysis. Research results showed that there is a relationship between market orientation, learning Orientation to business model innovation of restaurants and hotels in HCMC with significance level 0.01.